Pengaruh Kompensasi dan Pengembangan Karir terhadap Quality of Work Life pada Perawat Rumah Sakit di Kota Yogyakarta - Suhartini, Yati (Universitas PGRI Yogyakarta, 2020)
The research was conducted with the aim of knowing the influence of compensation and career development toward the quality of work life in the hospital nurses in Kota Yogyakarta. The sample of this research is 75 people, taken from a population of 284 people. Data was collected by applying questionnaires, analized by using multiple linier regression,and processed with the SPSS application program. Based on the result of data analysis, it was showed that the two independent variables, namely compensation (X1), and career development (X2),) influenced partially or simultaneously on quality of work life (Y), thus partially or simultaneously supporting the 3 hypotheses. Those were indicated by the value of regression coefficient and the significant level of each factor which are 0.227 and 0.009; 0,546 and 0,000, respectively. Likewise, the value of F amounting to 43,100 with the significance level of 0,000, whereas adjusted R2 counting to 0,532. Furthermore, career development indicates as the dominant variable that influences on the quality of work life.Keyword : compensation, career development, and the quality of work life